(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Acharya Susrutha has narrated Kshara as one of the Upayantras, Anusastras, Agropaharaniya and one of the Upakrama of Vrana. Kshara is considered superior to all surgical and para surgical measures. Kṣharas are more effective than other methods of treatment, because they can be used externally as Pratisaraniya Kshara and internally as Paneeya Kshara. Because of varied applications standardization of the compound formulation is the need of the present era to set standards for maintaining the quality of the products. In the present study work is done on the pharmaceutical and analytical study of Chincha Kshara conducted in the department of Shalya Tantra under the post graduate programme is being presented. Here an attempt has been made to study Chincha Kshara Analytically and to develop fingerprints by organoleptic tests, physico-chemical parameters and Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES).